Analisis Karakter Rasa Ingin Tahu Siswa Kelas VI pada Tema 5 Wirausaha di SD Supriyadi Semarang - Rohmawati, Linda; Setyawati, Rina Dwi; Subekti, Ervina Eka; Nafiah, Ulin (AS-SABIQUN, 2023)
Curiosity is a form of character education that must be improved for students in order to achieve life values to continue to be developed in one's personality, so that it becomes a habit in the behavior of students' daily lives. The results of pre-observations conducted on class VI students at SD Supriyadi Semarang showed that students' curiosity was not good with the following indicators: (1) students who actively asked were the same person, (2) there were some students who were not actively looking for good answers independent and group assignments (3) students are not active in group discussions, (4) students are less enthusiastic about the learning process, (5) students do assignments at will. The results of these pre-observations led the researcher to make an analysis of Curiosity in Grade VI students at SD Supriyadi which aims to find out the extent of students' curiosity in thematic learning theme 5 about Entrepreneurship. This study used a descriptive qualitative method with data collection techniques using the results of observations, interviews and questionnaires for students and then drawing conclusions. The results of this study indicate that the value of the curiosity character of class VI students at SD Supriyadi Semarang on theme 5 shows quite well. This can be seen from the most prominent indicator is the indicator of attention to the observed object which reaches a percentage of 59.4% while for the less prominent indicator in this study is the indicator asking about the material being studied which reaches a percentage of 28.1%.